Out-of-Step Relays Testing Procedure - Sauhats, Antans; Utans, Andrejs; Pashnin, Gregory; Antonovs, Dmitrijs (Electrical, Control and Communication Engineering, 2011)
The paper presents out-of-step (OOS) protection device testing methodology under close-to-real power system operation conditions. The power system stability modelling software is used as source of test signals. The accurate modelling of power system in conjunction with dynamical modelling features allows the correct choice of the most reliable OOS protection scheme. Methodology was applied for out-of-step relay "AGNA" testing and device settings verification.